Leukocyte entry into the CNS of Leishmania chagasi naturally infected dogs - Melo, G. D.; Marcondes, Mary [UNESP]; Vasconcelos, R. O. [UNESP]; Machado, Gisele Fabrino [UNESP] (Elsevier B.V., 2009)
In dogs, there is an association of chronic visceral leishmaniasis with neurological symptoms, and very few publications have investigated whether these neurological manifestations correlate with specific alterations in brain. A total of 42 mixed-breed adult dogs were selected from the Veterinary Hospital of UNESP-Aracatuba and the Control Zoonosis Center in Aracatuba, São Paulo State, Brazil, which is an endemic area for visceral leishmaniasis. Animals presenting positive ELISA and/or positive parasitological diagnosis of Leishmania were enrolled in the group of infected dogs (n = 32). Animals with negative ELISA results and parasitological tests for Leishmania, including a negative immunofluorescence test for toxoplasmosis and neosporosis, were included as the control group (n = 10). Brain samples were collected, stored in 10% buffered formalin and subjected to routine histological procedures, following by staining with haematoxylin-eosin (HE) and immunohistochemical examination for T and B lymphocytes and phagocytic cells. Cerebrospinal fluid was collected to determine the anti-Leishmania antibody titers. Histological examination of HE stains demonstrated intense inflammatory infiltrate, primarily in the choroid plexus, which was composed of mononuclear cells with no detectable parasites. Immunohistochemistry revealed that CD3(+) T lymphocytes were the major components of the inflammatory infiltrate at the choroid plexus and in the brain. Infected dogs had more CD3(+) T cells than uninfected animals (P = 0.0002). Cerebrospinal fluid from infected dogs contained high titers of anti-Leishmania antibodies in comparison with control animals (P<0.0001), which suggests a compromise of the blood-cerebrospinal fluid barrier. Leukocyte entry into the brain suggests the participation of these cells in the pathogenesis of neurological disorders during the advanced stages of leishmaniasis and confirms that the choroid plexus is an important structure for T cell influx. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Visceral Leishmaniasis; Central nervous system; Choroid plexus; Inflammation; T lymphocyte